Novel Chromatographic methodology for virus particles purification - Hamdi, Anis (2019)
"Virus based biopharmaceuticals are considered the most dynamic adopted tools in modern therapeutic medicine. Their use is increasing in the fields of vaccination and gene therapy. Membrane chromatography is becoming an attractive alternative t ool that can be used for virus purification due to its scalability, potential for optimization and economical features, allowing higher productivities with lower DSP costs. (…)"